1988
DOI: 10.1007/bf00917157
|View full text |Cite
|
Sign up to set email alerts
|

IgD/? plasmocytoma with immunoglobulin ? light-chain genes in the germ-line configuration

Abstract: Human immunoglobulin (Ig) genes are rearranged in an ordered sequence of events during B-cell differentiation: starting at the IgH locus, a productive VHDJH rearrangement leads to the expression of mu chains. Light-chain gene rearrangements have been found in pre-B cells which express mu chains. In these cells rearrangements of Ig kappa light-chain genes precede that of lambda genes. In an IgD/lambda-producing plasmocytoma, however, we found an apparent exception to this rule: the kappa genes were not rearrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…19 However, it is known that an IGL gene rearrangement can occasionally be present while the IGK genes are in germline configuration. 20 Until recently, allelic exclusion was generally regarded to be a safe mechanism that guarantees the expression of a single type of antigen receptor on each lymphocyte. However, during the last few years, several reports have indicated that dual receptor expression might occur in B lymphocytes as well as in T lymphocytes because of ongoing rearrangements after a functional receptor gene has been formed and expressed.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, it is known that an IGL gene rearrangement can occasionally be present while the IGK genes are in germline configuration. 20 Until recently, allelic exclusion was generally regarded to be a safe mechanism that guarantees the expression of a single type of antigen receptor on each lymphocyte. However, during the last few years, several reports have indicated that dual receptor expression might occur in B lymphocytes as well as in T lymphocytes because of ongoing rearrangements after a functional receptor gene has been formed and expressed.…”
Section: Introductionmentioning
confidence: 99%